Urban Development – the Social Dynamics of Transformation - Słaboń, Andrzej (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
In the paper urban development is understood as a chain of connected changes in the different spheres of inhabitants’ lives. Changes in urban areas depend on interactions between different actors. Foremost is the connection between the everyday behaviour of people and social changes. Individual behaviours are shaped by normative regulations, while excessive regulations lead to pacification and compensational reactions. Social dynamics of the changes in urban areas depend in many cases on the relationship between pacification processes and compensation.